2017
DOI: 10.1002/ejoc.201700933
|View full text |Cite
|
Sign up to set email alerts
|

From Chitin to α‐Glycosides of N‐Acetylglucosamine Using Catalytic Copper Triflate in a Heated Sealed‐Vessel Reactor

Abstract: The selective preparation of α‐glycosides of GlcNAc has been accomplished using a direct copper(II) triflate catalyzed glycosylation between α‐d‐glucosamine pentaacetate, readily available from chitin, and a range of alcohol acceptors. The α‐selectivity results from a post‐glycosylation anomerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…23 As shown in Scheme 1, compounds 2−22 were synthesized by microwave reaction described by Beau and co-workers to achieve α-glycosidation from galactosamine pentaacetate. 24 This one-step reaction avoids the use of 2-azido, 25 2,3-transoxazolidinone, 26 4,6-O-benzylidenyl, 27 4,6-O-di-tert-butylsilylene 28 or other nonparticipating temporary groups. By controlling the temperature and reaction time, we obtained the desired products in acceptable yields (38−61%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23 As shown in Scheme 1, compounds 2−22 were synthesized by microwave reaction described by Beau and co-workers to achieve α-glycosidation from galactosamine pentaacetate. 24 This one-step reaction avoids the use of 2-azido, 25 2,3-transoxazolidinone, 26 4,6-O-benzylidenyl, 27 4,6-O-di-tert-butylsilylene 28 or other nonparticipating temporary groups. By controlling the temperature and reaction time, we obtained the desired products in acceptable yields (38−61%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Generating selectively the α‐GlycNAc glycosides is a much more difficult task by this method. They are accessible only under more forceful conditions, generally resulting from a “thermal” anomerization of the initially formed β‐glycosides as with the iron(III) chloride/calcium sulfate (both in excess) procedure (Scheme ) or the catalytic copper(II) triflate in a heated sealed vessel procedure (Scheme ) . A single report has been given using stoichiometric ytterbium(III) triflate combined with catalytic BF 3 · Et 2 O (Scheme ) in which the phenol α‐glycosides would result from a direct S N 1‐type glycosylation from the α‐face of the glycosyl cation intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that copper(II) triflate activated as well the α‐peracetylated glucosamine 1α under catalytic conditions, furnishing a selective preparation of α‐glycosides . The starting material was easily obtained in pure form in one step from chitin acetolysis.…”
Section: Disarmed Glycnac Donorsmentioning
confidence: 99%
“…1-Phenyl-2-acetamido-3,4,6-tri-O-acetyl-2-deoxy-α-Dglucopyranose. 27 1 H), 5.20 (d, J = 8.2 Hz, 1 H), 5.07 (app t, J = 9.5 Hz, 1 H), 4.22 (dd, J = 12.2, 5.4 Hz, 1 H), 4.16-3.99 (m, 2 H), 3.90-3.70 (m, 1 H), 2.00 (s, 3 H), 1.99 (s, 3 H), 1.97 (s, 3 H), 1.88 (s, 3 H). 13 The title compound was prepared according to the general procedure from 1i (320 mg) and phenylboronic acid (185 mg) and was purified on silica gel chromatography (cyclohexane/EtOAc, (50/50) to afford 274 mg of an inseparable mixture of α and β anomers as an amorphous white solid (77%, α:β = 1.5:1 in NMR, 1.2:1 in HPLC).…”
Section: -Phenyl-2-acetamido-346-tri-o-acetyl-2-deoxy-dglucopyranose 4gmentioning
confidence: 99%